Sequence analysis of LipL41 and LipL21: Prospective Outer Membrane Proteins (OMPs) in early diagnosing leptospirosis - Mosquill, Muzaffar; Nordin, Syafinaz Amin; Mohd Ali, Mohamad Ridhuan; Joseph, Narcisse Mary Sither (Elsevier, 2022)
Leptospirosis is a zoonotic disease mostly occurring in tropical climate countries. The etiology of the disease is due to microbes from the genus Leptospira. Higher number of cases reported worldwide indicated the disease is not easily eradicated. Leptospirosis shares the most common febrile symptoms such as dengue, Zika and yellow fever thus making it difficult to differentiate the disease at an early stage. The widely used current detection via PCR, uses the bacterial outer membrane protein (OMP) as their target region. However, the heterogeneity and variation of the genome cause false negative results. Lipoprotein LipL41 is the third most abundant outer membrane lipoprotein among pathogenic species and it is surface exposed and expressed during infection thus making it a suitable candidate in identifying pathogenic Leptospira. LipL21 on the other hand is a potential candidate in identifying the intermediate species. The study aimed in designing suitable PCR primers in identifying pathogenic and intermediate species of Leptospira through bioinformatics analysis on the bacterial OMPs. LipL41 and LipL21 were chosen as the suitable target sequence to be used as PCR primers in detecting the pathogenic and intermediate species, respectively. The designed primers indicated positive feedback upon tested with their respective bacterial DNA extract. These lipoproteins may serve as potential PCR primers to be used with clinical samples in diagnosing leptospirosis.•The etiology of the illness is due to bacteria from the genus Leptospira.•PCR utilizes the bacterial external membrane protein (OMP) thus the heterogeneity and variety of the genome cause bogus adverse outcomes.•The suitable candidates are LipL41, the third most abundant outer membrane lipoprotein, whereas LipL21 is a potential candidate in identifying the intermediate species.